On the potential of using virtual reality for teacher education - Stavroulia, Kalliopi Evangelia; Lanitis, Andreas (My University, 2017)
Virtual reality technology has the potential to be used in teacher training as it can provide innovative virtual teaching environments, offering teachers the ability to gain in-training feedback and knowledge that can be transferred and applied to real-life situations. As part of an initial investigation into the applicability of using VR for teacher training, two experiments were conducted. The first experiment had to do with teachers’ understanding and detection of students’ possible disorders such as vision disorders. The second experiment had to do the ability of teachers to identify and deal with bullying-related activities among students. The results indicated that through a VR-based role-changing mechanism teachers could enter students’ position and understand their problems, while they experienced incidents that were like real-life incidents making the application a valuable training tool. The overall results of the preliminary investigations in combination with the findings of a related survey, highlight the potential of using VR for implementing real-life tools for teacher professional training. Building on the results of the preliminary experiments, a new application is currently under development aiming to address the lack of practice in teacher training and provide to young but also experienced teachers a VR-based school environment that represents real-life situations and will allow them to be trained, experiment, test their skills, make mistakes and learn from them but without the risk of harming real students.
Keywords: Head mounted display (HMD); Teacher preparation; Teacher training; Virtual classroom; Virtual reality